A many-objective evolutionary algorithm based on reference vector guided selection and two diversity and convergence enhancement strategies - Yang, Lei; Zhang, Yuanye; Cao, Jiale; Li, Kangshun; Wang, Dongya (Applied soft computing, 2024)
Achieving the balance between convergence and diversity is a key and challenging issue in many-objective optimization. Reference vector guided selection is an exemplary method for decomposition-based many-objective evolutionary algorithms (MaOEAs). However, there are some problems with it such as insufficient number of obtained solutions and inefficient convergence evaluation metric. Aiming at solving or alleviating these problems, this paper proposes a many-objective evolutionary algorithm based on reference vector guided selection and two diversity and convergence enhancement strategies. The proposed algorithm introduces two new strategies namely adaptive sparse region detection and convergence-only selection. The former is to adaptively detect sparse regions of current elite population, while the latter is to prevent the elimination of solutions with prominent convergence performance. Together with a newly proposed elite retention strategy, these two strategies can achieve diversity and convergence enhancement on the basis on reference vector guided selection. Besides, A new selection criterion for reference vector guided selection is proposed to better measure the convergence of solutions in high dimensionality. Experimental results on widely used test problem suites up to 15 objectives indicate that the proposed algorithm is highly competitive in comparison with seven state-of-the-art MaOEAs. •Two strategies based on reference vector guided selection for better performance.•An adaptive approach to detect sparse regions for diversity enhancement.•A method to preserve prominent solutions for convergence enhancement.•An elite retention strategy to fill vacancies in elite population.